MODEL IMPLEMENTASI KNOWLEDGE MANAGEMENT PADA PERUSAHAAN ENERGI (Studi Pada PT. Pertamina (Persero) dan PT. Medco Energi Internasional Tbk.) - Wulandari, Jeni (JURNAL PERSPEKTIF BISNIS, 2013)
This research aims to determine the implementation of knowledge management (KM) in energy companies such as PT. Pertamina (Persero) and PT. Medco EnergiInternasionalTbk., to know the critical success factors of KM implementation, and impact of KM implementation for the organization, and to formulate models of KM implementation in the organization. This research is a descriptive study with a qualitative approach. The data collected was used the literature study technique. This research is an extension of previous research on the proposed model of Organizational Knowledge Management System (OKMS).The results of this research indicate the implementation of KM in both energy companies includes: developing a corporate culture based on knowledge, innovation or products / services / solutions based on knowledge, maximize the companys intellectual capital, knowledge sharing or create an environment to share the knowledge with collaborative way, leadership-leadership factor which fully supports the KM activities, and learning- the methods of application which lead the company as a learning organization. The critical factors in the success implementation of KM is human (people), including leadership, infrastructure, process (learning), culture, and technology. Leadership and cultural factors are the main factors of success of KM implementation in the organization. The KM products as a result of the KM implementation is the process of learning (organizational learning) and the ability of innovation which is the value for the company to be able to kept the competitiveness. It is recommended that further research through questionnaires and in-depth interviews to test the model of KM implementation formulation.Â Keywords: Knowledge Management,Organizational Learning, Organizational Knowledge Management System (OKMS)